Risk Assessment Models of the Companies Implementing R&D Projects - V. В. Minasyan (Финансы: теория и практика)
Companies implementing R&D projects face their unique features. There is the need for large capital investments, long-term implementation, high growth potential, low probability of success, and diffculties in fnancing among them. Implementation of such projects is associated with high risks. This leads to underfunding as uncertain results deter investors. The problem of assessing the risks arising from the implementation of such projects has not yet been suffciently studied at the level of mathematical analysis models. The objective of the article is to develop a model allowing to explore the risks arising from implementing R&D projects. The author has developed a risk assessment model using the VaR measure modifed for this application. The formulas have been obtained to calculate this measure. They have been adjusted to simple analytical expressions assuming the balanced distribution of cash ﬂow from the project, or triangular distribution. The model considers the most important causes of risks in R&D projects. It can be used in a real-case scenario if a preliminary risk assessment of a project is done before its implementation and a decision is made on risk-based implementation. Moreover, this methodology can be used to standardize the decision-making process for the R&D projects implementation considering the “risk appetite” using the VaR risk measure.